When the Body Belies the Words: Embodied Agency With darf/kann ich? (“May/Can I?”) in German - Deppermann, Arnulf; Gubina, Alexandra (Frontiers in Communication, 2021)
Research on multimodal interaction has shown that simultaneity of embodied behavior and talk is constitutive for social action. In this study, we demonstrate different temporal relationships between verbal and embodied actions. We focus on uses of German darf/kann ich? (‘may/can I?’) in which speakers initiate, or even complete the embodied action that is addressed by the turn before the recipient’s response. We argue that through such embodied conduct, the speaker bodily enacts high agency, which is at odds with the low deontic stance they express through their darf/kann ich?-TCUs. In doing so, speakers presuppose that the intersubjective permissibility of the action is highly probable or even certain. Moreover, we demonstrate how the speaker’s embodied action, joint perceptual salience of referents, and the projectability of the action addressed with darf/kann ich? allow for a lean syntactic design of darf/kann ich?-TCUs (i.e., pronominalization, object omission, and main verb omission). Our findings underscore the reflexive relationship between lean syntax, sequential organization and multimodal conduct.